2011
DOI: 10.3892/ijo.2011.1091
|View full text |Cite
|
Sign up to set email alerts
|

Endosialin: A novel malignant cell therapeutic target for neuroblastoma

Abstract: Abstract. Endosialin emerged recently as a potential therapeutic target for sarcoma. Since some sarcoma subtypes, such as Ewing's sarcoma, show characteristics of neuroendocrine differentiation, we wondered whether cancers with neuroendocrine properties and/or neuroectodermal origin, such as neuroblastoma, small cell lung cancer and melanoma, may express endosialin. Endosialin protein expression was surveyed in neuroblastoma, small cell lung cancer and melanoma in human clinical specimens by immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…While other studies have demonstrated endosialin staining on pediatric tumor cells, there is often a high degree of variability of expression within and across tumor types. 6,8 However, consistent with our findings, these studies demonstrate that even if endosialin is not expressed on the malignant cells, there is consistent and strong expression on the tumor stroma and vasculature, supporting a possible role therapeutic role of ontuxizumab in the disruption of tumor organization. Therefore, while no objective responses were observed in this study, based on the mechanism of action, lack of myelosuppression and tolerability, the evaluation of ontuxizumab in combination with chemotherapy or radiation with stratification based on serum PDGFRβ levels may be considered.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While other studies have demonstrated endosialin staining on pediatric tumor cells, there is often a high degree of variability of expression within and across tumor types. 6,8 However, consistent with our findings, these studies demonstrate that even if endosialin is not expressed on the malignant cells, there is consistent and strong expression on the tumor stroma and vasculature, supporting a possible role therapeutic role of ontuxizumab in the disruption of tumor organization. Therefore, while no objective responses were observed in this study, based on the mechanism of action, lack of myelosuppression and tolerability, the evaluation of ontuxizumab in combination with chemotherapy or radiation with stratification based on serum PDGFRβ levels may be considered.…”
Section: Discussionsupporting
confidence: 87%
“…15 Preclinical investigations have demonstrated strong endosialin expression in pediatric malignancies including Ewing sarcoma, osteosarcoma, rhabdomyosarcoma, synovial sarcoma, and neuroblastoma. 68 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the majority of human tumours of epithelial origin where endosialin expression is not detected on the tumour cells, tumour cell endosialin expression has been reported in a subset of neuroblastomas ( Rouleau et al , 2011 ) and sarcomas. Regarding the latter, Rouleau et al assessed the immunohistochemical expression of endosialin on 86 formalin-fixed, paraffin-embedded human clinical sarcoma specimens ( Rouleau et al , 2008 ), and documented expression in different cell types; 51% (54/86) showed endosialin expression in malignant cells, 78% (67/86) in vasculature and 22% (19/86) in stromal cells.…”
Section: Discussionmentioning
confidence: 77%
“…In epithelial neoplasias, expression of endosialin is typically detected on stromal fibroblasts and tumour vessel-associated pericytes ( MacFadyen et al , 2005 ; Rupp et al , 2006 ; MacFadyen et al , 2007 ; Bagley et al , 2008 ; Christian et al , 2008 ; Simonavicius et al , 2008 ) but not in the tumour cell compartment or endothelium ( MacFadyen et al , 2005 ; Bagley et al , 2008 ; Christian et al , 2008 ; Simonavicius et al , 2008 ). This upregulated stromal expression of endosialin has been reported in a wide range of human cancers, including breast carcinomas ( Rouleau et al , 2008 ), ovarian epithelial, colonic and rectal carcinomas ( Bagley et al , 2008 ), small cell lung cancer, neuroblastoma and melanoma ( Rouleau et al , 2011 ), metastatic melanomas and squamous cell carcinomas ( Huber et al , 2006 ), high grade gliomas/glioblastoma multiforme, anaplastic astrocytomas and metastatic carcinomas to brain ( Brady et al , 2004 ; Simonavicius et al , 2008 ). While its function in these stromal cells is yet to be clearly defined, knockout mouse models have shown the absence of endosialin expression results in reduced growth, invasion and metastasis of human tumour xenografts ( Nanda et al , 2006 ; Tomkowicz et al , 2007 ), with increase in small immature vessels and decrease in medium and large tumour vessels, suggesting a role in controlling the interaction between tumour cells, endothelia and the extracellular matrix.…”
Section: Discussionmentioning
confidence: 79%
“…Endosialin expression is essentially restricted to activated cells of the mesenchymal lineage, including pericytes and myofibroblasts during embryogenesis [ 1 3 ]. Importantly, expression of endosialin is dramatically reduced in adults, but has been shown to be up-regulated during pathologic states, including tumor progression and metastasis [ 4 , 5 ] making endosialin an oncofetal protein with potential as therapeutic target [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%